2011
DOI: 10.1103/physrevlett.107.076801
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Weak Localization and Antilocalization in Topological Surface States

Abstract: A magnetoconductivity formula is presented for the surface states of a magnetically doped topological insulator. It reveals a competing effect of weak localization and weak antilocalization in quantum transport when an energy gap is opened at the Dirac point by magnetic doping. It is found that, while random magnetic scattering always drives the system from the symplectic to the unitary class, the gap could induce a crossover from weak antilocalization to weak localization, tunable by the Fermi energy or the g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
360
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(385 citation statements)
references
References 46 publications
19
360
3
3
Order By: Relevance
“…Since ARPES measurements show that the Fermi level in these samples is located well in the bulk conduction band states, the magnetoconductance data probe a complicated interplay between states that include the pure TI surface, confined two dimensional (2D) states created by band bending and three dimensional (3D) bulk states. Despite this complex situation, the onset of time reversal symmetry breaking ferromagnetism qualitatively yields the magnetoconductance behavior predicted for 2D Dirac cone TI surface transport 18 . We note that a recent study 19 of ultrathin (3 QL) samples of Cr-doped Bi 2 Se 3 showed a similar cross-over from weak anti-localization to weak localization, but in a regime where the samples are paramagnetic and where a surface state gap is already developed at a temperature (∼ 100 K) much higher than that implied by transport measurements ( 10 K).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Since ARPES measurements show that the Fermi level in these samples is located well in the bulk conduction band states, the magnetoconductance data probe a complicated interplay between states that include the pure TI surface, confined two dimensional (2D) states created by band bending and three dimensional (3D) bulk states. Despite this complex situation, the onset of time reversal symmetry breaking ferromagnetism qualitatively yields the magnetoconductance behavior predicted for 2D Dirac cone TI surface transport 18 . We note that a recent study 19 of ultrathin (3 QL) samples of Cr-doped Bi 2 Se 3 showed a similar cross-over from weak anti-localization to weak localization, but in a regime where the samples are paramagnetic and where a surface state gap is already developed at a temperature (∼ 100 K) much higher than that implied by transport measurements ( 10 K).…”
Section: Introductionmentioning
confidence: 78%
“…We now discuss an interpretation of these data based upon diagrammatic calculations 18,28 for quantum corrections to transport in Bi 2 Se 3 . In samples such as the ones studied here, the bulk states dominate the conductivity because of the large Fermi energy: a simple estimate using the surface state energy dispersion and a Fermi energy 300 meV above the Dirac point shows that the surface carrier density (∼ 1.3 × 10 13 cm −2 ) is about an order of magnitude smaller than that of the bulk in our samples.…”
Section: Transport Measurements: Observation Of Ferromagnetism Anmentioning
confidence: 99%
“…In addition, as it has been shown recently, the opening of the gap in the Dirac bands may actually change the sign in the quantum correction to conductivity from weak-antilocalization to weak localization. 25 Perhaps the fact that this crossover has not been observed 31 suggests that at least one of the Dirac bands remains ungapped.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of the spin-orbit interaction for the surface electrons in topological insulators can be indirectly probed by studying the quantum interference correction to conductivity: [24][25][26][27][28] upon decrease in temperature, δT < 0, increase in conductivity (δσ > 0) would signal weak anti-localization effect as opposed to weak localization corresponding to decrease in conductivity (δσ < 0). The sign of the correction to conductivity is determined by the ratio of the spin-orbit scattering length, l SO , to the dephasing length l φ : for weak spin-orbit coupling, l SO l φ (here l is a mean-free path) correction to conductivity is negative, while in the opposite limit of strong spin-orbit coupling l SO l φ and the interference correction to conductivity is positive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation